Partisan Federalism and Subnational Governments' International Engagements: Insights from India. Issue 4 (18th June 2020) - Sharma, Chanchal Kumar; Destradi, Sandra; Plagemann, Johannes
Abstract: This article situates the international activities of subnational governments in India within the broader political economy of federalism. It argues that the nature and the extent of subnational states' engagements in international affairs are a function of the partisan political relationship the state incumbents have with the national incumbents. The article takes a mixed methods approach. An analysis of 1, 153 episodes of international engagements of India's states from 1996 to 2017 reveals that shifts in foreign policy engagement of selected state governments primarily reflect alterations in the subnational incumbents' political affiliation with the Union government. Several qualitative case studies shed light on how the central government's inclusion of subnational governments' perspectives and representatives in foreign affairs is highly partisan and profoundly political. Therefore, the Indian case reveals how subnational diplomatic interactions merge domestic and international politics.